Leaf epidermis micromorphology characters of 18 species of Microlepia from China and its taxonomic significance - Renxiang WANG; Ling LIU (Guangxi Zhiwu, 2023)
The fern genus Microlepia is a natural fern group, while large morphological differences of this genus lead to some classification controversies. The leaf epidermal micromorphology of 18 species (include 3 varieties) of Microlepia was observed and compared under light microscope (LM) and scanning electron microscope (SEM). Hairs were on the veins of the upper and lower epidermis. The form of epidermal cells was irregular, with the anticlinal walls sinuous or sinuate. The stomatal apparatus of all species were restricted to abaxial epidermises and generally could be described as polocytic and axillocytic type, and copolocytic, coaxillocytic, aisocytic and anomotetracytic type only appears in a few species. The similarity of the micromorphological characteristics of leaf epidermis support that the genus Microlepia is a monophyletic group in Dentaedtiaceae. The hairs characteristics between veins of the leaves support that M. calvescens, M. marginata var. villosa and M. marginata var. bipinnata should be treated as a variety of M. marginata. Under SEM, the cuticle of the upper epidermis was mostly ridged, and most of them had filiform ornamentation. The characteristics of leaf cuticle ornamentation were correlated with pinnate compound leaves. The inner margin of the outer stomatal rim was often smooth, sinuous or odontoid. “T” sharp, upright outer stomatal rims occurred in most species, and outer stomatal ledge was mostly depressed. The differences among the leaf micromorphology of these species were shown, which provides references for the classification, evolution and system location of Microlepia.